(untitled) (Jurnal Intek Akuakultur, 2019)
This study aims to evaluate how the different types of feed influence the addition of papain enzymes to improve feed efficiency and growth of groupers. The research design was a completely randomized design with 4 treatments and 3 replications of the best results were pellet treatment without enzymes (feed efficiency (55.4 Â± 12.45%), feed conversion ratio (1.8), absolute growth (20.89 Â± 4.44g), daily growth (0.7 g / day) and survival (98.33%).